A three-dimensional perspective on how land use/cover change reshapes drought propagation under climate change? - Hongguang Chen; Fanhao Meng; Chula Sa; Min Luo; Yuhai Bao; Tie Liu (Journal of Hydrology: Regional Studies, 2025)
Study regions: Beijing-Tianjin-Hebei (BTH), China Study focus: With climate change and intensified human activities, drought propagation has become more complex, and it is crucial to reveal its spatial and temporal distribution characteristics and driving factors. In this study, we analyzed the meteorological-hydrological drought propagation process in BTH from 1960 to 2020 based on the standardized precipitation index (SPI) and standardized runoff index (SRI). Through the drought propagation identification method and migration model, we identified four drought propagation types and investigated their propagation angles, directions, distances and paths. Meanwhile, the effects of meteorological factors and land use changes on drought propagation were quantified New hydrological insights for the region: Both SPI (0.138/10a) and SRI (0.21/10a) showed a drying trend, with the strongest trend in northern BTH. SPI events were more frequent (>83 events), longer in duration (9.37 months), and less intense than SRI events. We identified 23 drought propagation events, primarily from single SPI to single SRI, with multiple SPI to one or more SRI events becoming more common after 2000. Drought propagation time (DPT) averaged 1 month but increased to 6 months post-2000, while the Drought Propagation Index (DPI) dropped to 1.2. Droughts mainly propagated northward, covering the longest distance (612.14 km). Precipitation and temperature were key factors influencing the distance of propagation (DPdist), while land use/cover changes affected the drought propagation angle (DPA) and time (DPT).